2015
DOI: 10.1002/zoo.21245
|View full text |Cite
|
Sign up to set email alerts
|

Diets high in fruits and low in gum exudates promote the occurrence and development of dental disease in pygmy slow loris (Nycticebus pygmaeus)

Abstract: Asian slow lorises are found in zoos and rescue centres worldwide with Nycticebus pygmaeus, the pygmy slow loris, boasting the largest population in captivity. Diet are reportedly high in fruit and concentrates and low in insects and exudates. Wild feeding studies place insects, nectar, and gums as the most important diet components. Captive populations also show high incidences of health afflictions, many of which may be caused by nutrition. Our study, aims at identifying a causative agent within the diets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 36 publications
(63 reference statements)
0
44
0
Order By: Relevance
“…Indeed, 71% of the species listed in Tables 1-3 are found in captive settings, either as part of a managed breeding program in accredited zoological institutions worldwide or in rescue centres being rehabilitated and reintroduced. Wild diets are often the first step when formulating a diet, as well as using domestic or laboratory animal models to determine specific nutrient requirements (Cabana & Nekaris 2015). Many accrediting zoo bodies now produce their own husbandry/ best practice guidelines for holders, or endorse studies or guides put together by outside organizations.…”
Section: Gum-eating Mammals In Captivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, 71% of the species listed in Tables 1-3 are found in captive settings, either as part of a managed breeding program in accredited zoological institutions worldwide or in rescue centres being rehabilitated and reintroduced. Wild diets are often the first step when formulating a diet, as well as using domestic or laboratory animal models to determine specific nutrient requirements (Cabana & Nekaris 2015). Many accrediting zoo bodies now produce their own husbandry/ best practice guidelines for holders, or endorse studies or guides put together by outside organizations.…”
Section: Gum-eating Mammals In Captivitymentioning
confidence: 99%
“…Because they include obligate or facultative feeders, husbandry recommendations for the Callitrichidae and Lorisidae should include gum in their diets. Cabana and Nekaris (2015) provided evidence that diets high in fruit and low in gum contribute to dental disease in Nycticebus. The free-ranging diet of Nycticebus javanicus significantly differs between rehabilitated and released individuals versus wild individuals (Rode-Margonno et al 2014).…”
Section: Gum-eating Mammals In Captivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies where gluten free diets were shown to be beneficial for MWS, the fiber content was also increased and this may have contributed to their positive results (Kuehnel et al, 2013). Removing or reducing fruit from diets and replacing them with vegetables will also reduce soluble carbohydrates and increase fiber fractions, perhaps giving the same positive results (Britt et al, 2015;Cabana & Nekaris, 2015).…”
Section: The Fiber Hypothesismentioning
confidence: 96%
“…Stepsirhines are particularly affected, especially Nycticebus spp. due to their specific exudativorous feeding ecology and abundance of health issues observed in captivity (Cabana & Nekaris, ).…”
Section: Introductionmentioning
confidence: 99%